Comparative Scanning Electron Microscopy Study on Scale Variations in Indonesian Cultivated Koi Fish (Cyprinus rubrofuscus Lacepede, 1803) - Andrian, Krisna Noli; Wihadmadyatami, Hevi; Wijayanti, Nastiti; Karnati, Srikanth; Haryanto, Aris (Universitas Airlangga, 2025)
Koi (Cyprinus rubrofuscus Lacepede, 1803) is a highly favored ornamental fish due to its beauty and wide range of variations in Indonesia, categorized by color, patterns, and scales. Some variants are distinguished by color, while others, such as Ginrin, Doitsu, and Shusui, have unique scale types. Despite visible differences, microscopic scale variations remain unexplored. SEM studies in other fish species offer insights into scale ultrastructure, providing opportunities for comparison. Therefore, this study aimed to uncover the microscopic structure of four types of koi fish, namely Doitsu, Ginrin, Shusui, and common scale. Koi fish were obtained from breeders in Yogyakarta, Indonesia, and acclimatized in an aquarium. Scale extraction was conducted under anesthesia using MS-222 and the cleaned scales were then subjected to dehydration, fixation, and affixed to double-sided adhesive tape for SEM analysis. Furthermore, coating with conductive gold enabled observation using SEM at 10 kV, allowing examination of scale features such as focus, radii, circuli, and lepidonts at various magnifications. The results showed that based on SEM analysis, significant differences were observed in scale structures among koi variants. At low magnification, differences in tubercles and lepidonts were observed, particularly between common and Ginrin scale types. Shusui scale showed unique characteristics with a closer arrangement of circuli and distinctive lepidont shapes. At higher magnification, clearer details of radii, circuli, and lepidonts were observed, further highlighting the differences among koi variants. SEM provides crucial insights into the morphology of scales in koi fish variants, showing unseen macroscopic differences and distinct features such as tubercles and lepidont frequency.